CARBOHYDRATES AND GI: A COMPARATIVE STUDY OF TROPICAL AND TEMPERATE ROOT CROPS - Apurwa Singh; Sanyogita Shahi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Root crops are global staples, and their impact on human health and nutrition is fundamentally shaped by their carbohydrate content. This review presents a comparative analysis of 15 major tropical and temperate root crops, exploring their carbohydrate composition, glycaemic index (GI), and culinary use. As global staples, their nutritional and physiological effects are directly linked to their carbohydrate profiles. After examining variations in starch and sugar content, the influence of processing methods on GI values, and the resulting implications for their culinary uses and health benefits. Our findings reveal that tropical roots, such as cassava and yams, are characterized by high starch content and a corresponding high GI. Similarly, temperate crops like potatoes also have a high but variable GI, largely dependent on preparation methods. In contrast, other crops, such as sweet potatoes and jicama, possess higher simple sugar and dietary fibre content, respectively, contributing to their lower GI values and diverse culinary applications. Rhizomes like ginger and turmeric are not significant energy sources; their low carbohydrate content makes them valuable as flavour agents and for their ability to modulate GI in other foods. This study concludes that a root crop’s botanical origin and geographic location are key determinants of its carbohydrate composition, which in turn dictates its GI and its essential role in human health and diet.